“Lights and Shadows”: An Interpretative Phenomenological Analysis of the Lived Experience of Being Diagnosed With Breast Cancer During Pregnancy - Facchin, Federica; Scarfone, Giovanna; Tamanza, Giancarlo; Ravani, Silvia; Francini, Federica; Peccatori, Fedro Alessandro; Di Loreto, Eugenia; Dell’Acqua, Andrea; Saita, Emanuela (Frontiers in Psychology, 2021)
Cancer diagnosed during pregnancy is a rare event. The most common type of malignancy diagnosed in pregnant women is breast cancer, whose incidence is expected to raise in the next future due to delayed childbirth, as well as to the increased occurrence of the disease at young age. Pregnant women diagnosed with breast cancer are exposed to multiple sources of stress, which may lead to poorer obstetric outcomes, such as preterm birth and low birth weight. In addition, pregnancy involves physiological changes in the breasts that may blur the signs of cancer, with delayed diagnosis and poor prognosis. However, the lived experience of these women was investigated in very few studies. Given this scenario, we conducted this qualitative study to describe and understand women’s subjective experience of being diagnosed with breast cancer during pregnancy. The study was conducted following the principles of Interpretative Phenomenological Analysis. Participants were five women with breast cancer diagnosed during pregnancy, purposefully recruited at a public hospital during medical visits and interviewed at treatment initiation. The interview transcripts were analyzed using thematic analysis. The textual analysis led to the identification of three main themes related to: (1) the emotional storm experienced after cancer diagnosis, and the importance of receiving appropriate information and being focused on treatment decisions; (2) physical changes and comparisons with healthy women, associated with feelings of sadness and inadequacy; (3) being positive, feeling free to disclose all kinds of emotions, religion and spirituality as sources of strength. The paradoxical coexistence of pregnancy and cancer represents a stressful experience for women and their loved ones. Adopting a systemic perspective may be important to understand the effects of such a complex condition, also considering its impact on healthcare workers.